HR Metrics and Analytics for Strategic Decision Making (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
This research paper provides a comprehensive review of HR metrics and analytics in the context of strategic decision making. The paper explores the significance of leveraging HR data and analytics to inform strategic decisions and drive organizational success. It delves into the various types of HR metrics and analytical techniques used to measure and analyze HR performance, employee engagement, talent management, and workforce effectiveness. The paper also highlights the challenges and opportunities associated with HR analytics adoption and offers recommendations for organizations seeking to harness the power of HR metrics and analytics to enhance their strategic decision-making capabilities.